Consumer‐assisted selection: the preference for new tablegrape cultivars in China. (6th August 2015) - Zhou, J.; Cao, L.; Chen, S.; Perl, A.; Ma, H.
Abstract Background and Aims Many new grape breeding lines with diverse quality attributes are becoming available every year. The search for specific markets is both time‐consuming and labour‐intensive. Consumer‐assisted selection could help improve breeding and marketing efficiency. Methods and Results Three hundred and fifteen Chinese consumers were surveyed in Beijing; 69 of them further taste‐tested ten grape samples to understand consumer preferences for tablegrape cultivars and the key attributes influencing their choice. The participants mostly preferred medium size, completely closed bunches with a tight shoulder and bunches of red to dark‐coloured round or oval berries with an intense sweet–sour flavour. Intense juiciness, a crunchy texture, seedlessness and 'Muscat' aroma were supportive attributes. Conclusions Specific preferences for extrinsic and intrinsic attributes of tablegrapes were found in Chinese consumers. Consumer‐assisted selection could help improve the efficiency of breeding and targeted marketing. Significance of the Study This study provides the first set of consumer‐assisted tablegrape‐selection data in China, which can be used as a reference in the breeding of new grape cultivars and in enhancing grape competitiveness in the Chinese market.